Complications of Tranexamic Acid in Orthopedic Lower Limb Surgery: A Meta-Analysis of Randomized Controlled Trials. (18th January 2021) - Reale, Davide; Andriolo, Luca; Gursoy, Safa; Bozkurt, Murat; Filardo, Giuseppe; Zaffagnini, Stefano
Abstract : Objective . Tranexamic acid (TXA) is increasingly used in orthopedic surgery to reduce blood loss; however, there are concerns about the risk of venous thromboembolic (VTE) complications. The aim of this study was to evaluate TXA safety in patients undergoing lower limb orthopedic surgical procedures. Design . A meta-analysis was performed on the PubMed, Web of Science, and Cochrane Library databases in January 2020 using the following string (Tranexamic acid) AND ((knee) OR (hip) OR (ankle) OR (lower limb)) to identify RCTs about TXA use in patients undergoing every kind of lower limb surgical orthopedic procedures, with IV, IA, or oral administration, and compared with a control arm to quantify the VTE complication rates. Results . A total of 140 articles documenting 9, 067 patients receiving TXA were identified. Specifically, 82 studies focused on TKA, 41 on THA, and 17 on other surgeries, including anterior cruciate ligament reconstruction, intertrochanteric fractures, and meniscectomies. The intravenous TXA administration protocol was studied in 111 articles, the intra-articular in 45, and the oral one in 7 articles. No differences in terms of thromboembolic complications were detected between the TXA and control groups neither in the overall population (2.4% and 2.8%, respectively) nor in any subgroup based on the surgical procedure and TXA administration route. Conclusions . There is an increasing interest in TXA use, which has been recently broadened from the most common joint replacement procedures to the other types of surgeries. Overall, TXA did not increase the risk of VTE complications, regardless of the administration route, thus supporting the safety of using TXA for lower limb orthopedic surgical procedures.